An application of incremental scheduling to a cluster photolithography tool - Ware, Simon (2020)
Optimization is an important area of research. As many optimization problems are NP-Hard it is important to have a wide selection of heuristic approaches to choose from when solving problems. Prioritized planning is a technique traditionally used to solve the multi-robot path planning problem. In this paper we investigate how incremental scheduling, a technique based upon prioritized planning can be applied to scheduling wafer processing in a cluster tool. For our test case our approach is shown to be capable of finding a plan of equal quality to other scheduling approaches and thus suggests our method could be of potential use in other manufacturing/material handling applications.